Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
![](https://rs.olm.vn/images/avt/0.png?1311)
PTĐTTNT?
1.Đặt \(a^2+a=t\)
\(\Rightarrow\left(a^2+a\right)\left(a^2+a+1\right)-2\)
\(=t\left(t+1\right)-2\)
\(=t^2+t-2\)
\(=t^2+2t-\left(t+2\right)\)
\(=t\left(t+2\right)-\left(t+2\right)\)
\(=\left(t+2\right)\left(t-1\right)\)
Sửa đề:
\(x^4+2011x^2+2010x+2011\)
\(=\left(x^4-x\right)+2011x^2+2011x+2011\)
\(=x\left(x^3-1\right)+2011\left(x^2+x+1\right)\)
\(=x\left(x-1\right)\left(x^2+x+1\right)+2011\left(x^2+x+1\right)\)
\(=\left(x^2+x+1\right)\left(x^2-x+2011\right)\)
3. \(\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)-120\)
\(=\left(x^2+5x+4\right)\left(x^2+5x+6\right)-120\)
Đặt \(x^2+5x+4=t\)
\(\Rightarrow\left(x+1\right)\left(x+2\right)\left(x+3\right)\left(x+4\right)-120\)
\(=t\left(t+2\right)-120\)
\(=t^2+2t+1-121\)
\(=\left(t+1\right)^2-11^2\)
\(=\left(t+1-11\right)\left(t+1+11\right)\)
\(=\left(t-10\right)\left(t+12\right)\)
\(=\left(x^2+5x-6\right)\left(x^2+5x+16\right)\)
\(=\left[\left(x^2-x\right)+\left(6x-6\right)\right]\left(x^2+5x+16\right)\)
\(=\left[x.\left(x-1\right)+6\left(x-1\right)\right]\left(x^2+5x+16\right)\)
\(=\left(x-1\right)\left(x+6\right)\left(x^2+5x+16\right)\)
4. \(\left(x^2+x+4\right)^2+8x\left(x^2+x+1\right)+15x^2\)
\(=\left(x^2+x+4\right)^2+2.\left(x^2+x+1\right).4x+\left(4x\right)^2-x^2\)
\(=\left(x^2+x+4+4x\right)^2-x^2\)
\(=\left(x^2+4+5x-x\right)\left(x^2+5x+x+4\right)\)
\(=\left(x^2+4x+4\right)\left(x^2+6x+4\right)\)
\(=\left(x+2\right)^2\left[\left(x^2+2.x.3+3^2\right)-\left(\sqrt{5}\right)^2\right]\)
\(=\left(x+2\right)^2\left[\left(x+3\right)^2-\left(\sqrt{5}\right)^2\right]\)
\(=\left(x+2\right)^2\left(x+3-\sqrt{5}\right)\left(x+3+\sqrt{5}\right)\)
![](https://rs.olm.vn/images/avt/0.png?1311)
6) c) x3 - x2 + x = 1
<=> x3 - x2 + x - 1 = 0
<=> (x3 - x2) + (x - 1) = 0
<=> x2 (x - 1) + (x - 1) = 0
<=> (x - 1) (x2 + 1) = 0
=> x - 1 = 0 hoặc x2 + 1 = 0
* x - 1 = 0 => x = 1
* x2 + 1 = 0 => x2 = -1 => x = -1
Vậy x = 1 hoặc x = -1
Bài 5:
a) Đặt \(A=\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=\left(3^2-1\right)\left(3^2+1\right)\left(3^4+1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=\left(3^4-1\right)\left(3^4+1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=\left(3^8-1\right)\left(3^8+1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=\left(3^{16}-1\right)\left(3^{16}+1\right)\)
\(\Rightarrow8A=3^{32}-1\)
\(\Rightarrow A=\frac{3^{32}-1}{8}\)
b) (7x+6)2 + (5-6x)2 - (10-12x)(7x+6)
=(7x+6)2 + (5-6x)2 - 2(5-6x)(7x+6)
\(=\left(7x+6-5+6x\right)^2\)
\(=\left(13x+1\right)^2\)